Determinan Minat Masyarakat Menggunakan Layanan Syariah Link Aja - Silahuddin Silahuddin; Maslichah Maslichah; Junaidi Junaidi (Universitas Islam Malang, 2021)
This study aims to analyze and determines the determinants of public interestin using sharia Link Aja service. This study belongs to quantitative associativeresearch. The sampling technique was carried out using the Slovin formula. Therewere 100 respondents from the Malang City community who only use sharia Link Ajaservice. The data was analysed by using multiple linear regression analysis usingSPSS 14. The results showed that the perceived usefulness variable (X1) had apositive and significant effect on interest in using (Y), the perceived trust variable(X2) had a positive and significant effect on interest in using (Y), subjective normvariable (X3) had a positive and significant effect on interest in using (Y).